ALBI Score for Predicting Acute Liver Failure in Patients with Acute Hepatitis B and D in Mongolia (Central Asian Journal of Medical Sciences, 2021)
Objectives: Mongolia is known as one of the countries with a high prevalence of hepatitis B and D virus infection. Although the number of acute hepatitis D cases is decreasing since the national vaccination program against HBV launched in 1991, it is still a main cause of acute liver failure (ALF) in Mongolia. The aim of this study is to determine the prognostic value of an ALBI score in patients with acute hepatitis B with or without D. Methods: A total of 114 patients (58 patients with acute hepatitis B (AHB), five patients with HBV/HDV co-infection, and 51 patients with HBV/HDV superinfection), who were admitted to the National Center for Communicable Diseases between 2017 and 2019 were enrolled into this study. Results: We compared the AHB group to the HBV/HDV superinfection group. The mean age was 25.8±6.5 years in the AHB group vs. 28.9±7.4 years in the HBV/HDV superinfection group (p = 0.019). Also, a majority of patients live in Ulaanbaatar (87.5% vs. 62.7%, p = 0.037). The mean hospitalization days was 23± 11 in the AHB, on the other hand it was 28± 13 in the HBV/HDV superinfection group (p = 0.022). The ALF patients had a higher ALBI score, total bilirubin, transaminase, and INR compared with the non-ALF group. The platelet count was significantly lower in the AHB and HBV/HDV infection group with ALF compared with AHB and HBV/HDV infection without ALF. This study showed that the ALBI score in AHB with ALF patients was significantly higher than in AHB without ALF (p = 0.001 ), and H BV/HDV superinfection with ALF had a higher ALBI score than HBV/HDV superinfection without ALF (p = 0.041 ). The area under the curve (AUC) value was 0.766 for ALBI scores. The cut-off value, sensitivity and specificity of ALBI score values were -1. 71, 72.2%, and 75.6%, respectively. Conclusions: ALBI score determined on admission indicates the likelihood of survival of patients with AHB and AHD.